Knowledge transfer interventions on cancer in Africa and Asia: a scoping review - (:unkn) unknown (My University, 2025)
Background: Cancer is a growing public health concern in Africa and Asia, where access to effective healthcare and resources is often limited. There is an urgent need for evidence-based cancer control policies in Africa and Asia, along with systems for prevention, early detection, diagnosis and treatment, and palliative care. This emerging issue has garnered growing interest from international institutions but there has been little visible action, and the existing knowledge remains scattered and fragmented. This scoping review aims to explore the breadth and scope of evidence regarding knowledge transfer interventions to enhance cancer care in Africa and Asia.Methods : We conducted a systematic search of Embase, Emcare, ERIC, APA PsycInfo, Medline, and Google Scholar, supplemented by expert bibliographies and references. Peer-reviewed empirical studies in English or French from January 1978 to September 2024 were included. Data were organised using the AIMD (Aims, Ingredients, Mechanism & Delivery) framework. Study quality was presented using the Mixed Methods Appraisal Tool.Results : The scoping review examined seven articles providing evidence on five unique interventions. The interventions included target both decision-makers and health professionals and aim to strengthen evidence-based cancer control policies and implementation strategies. The interventions documented have all been initiated by external actors, mainly international institutions or researchers from high-income countries, in collaboration with African and Asian stakeholders. In addition, some researchers have been involved in participatory research projects designed to enable decision-makers to implement evidence-based cancer control policies and programmes.Conclusions : This scoping review highlights a critical lack of evidence on knowledge transfer interventions in cancer care across Africa and Asia, partly due to limited funding for non-communicable diseases. It calls
Keywords: African Research